Experimental validation of the analytical model for tungsten dust - wall mechanical impacts incorporated in the MIGRAINe dust dynamics code. (August 2017) - Tolias, P.; Ratynskaia, S.; Shalpegin, A.; Vignitchouk, L.; Brochard, F.; De Angeli, M.; van der Meiden, H.
Highlights: In-plasma dust-surface impacts recorded with unprecedented resolution. Experimental determination of the normal and tangential restitution coefficients. Validation of the dominance of plastic/adhesive work over frictional dissipation. Calibration of the analytical impact model of the MIGRAINe dust-dynamics code. Abstract: Mechanical dust-wall collisions are unavoidable in fusion devices and their accurate modeling is essential for the understanding of dust transport. The MIGRAINe dust dynamics code features analytical models addressing all facets of dust-surface impacts, some aspects of which have not been experimentally validated thus far. Dedicated dust injection experiments have been carried out in Pilot-PSI resulting to the visualization of in-plasma tungsten dust-surface impacts with an unprecedented resolution. They allowed for a calibration of key quantities of the MIGRAINe impact model.